Decreased Neurogenesis Increases Spatial Reversal Errors in Chickadees (Poecile atricapillus). Issue 12 (5th October 2018) - Guitar, Nicole A.; Sherry, David F.
Abstract: Adult hippocampal neurogenesis has been proposed to both aid memory formation and disrupt memory. We examined the role of adult hippocampal neurogenesis in spatial working and reference memory in black‐capped chickadees ( Poecile atricapillus ), a passerine bird that relies on spatial memory for cache retrieval and foraging. We tested spatial working and spatial reference memory in birds that had received methylazoxymethanol acetate (MAM), a neurotoxin that decreases hippocampal neurogenesis. MAM treatment significantly reduced neurogenesis in the hippocampus quantified by doublecortin (DCX) labeling of newly divided and migrating neurons. MAM treatment had little effect on the working or reference memory but caused an increase in errors on the reference memory task following reversal. Working memory for recently visited spatial locations and reference memory for familiar spatial locations were thus unaffected by a reduction in neurogenesis. An increase in errors following reference memory reversal may indicate that adult hippocampal neurogenesis aids in pattern separation, the differentiation of similar memories at the time of encoding.